Analisis Faktor-Faktor Yang Mempengaruhi Perilaku Kader Pkk Terhadap Perawatan Rambut (Studi Kasus Di Rw 07 Kelurahan Lenteng Agung) - Puspasari, Annisa Indah; Supiani, Titin; Jubaedah, Lilis (Peneliti.net, 2023)
The DKI Jakarta Provincial Government needs the presence of PKK cadres who are burdened with certain tasks to participate in the successful implementation of the PKK main program in order to create a prosperous and happy Jakarta. The tasks assigned to PKK cadres are not easy and take up a lot of their time. This can make PKK cadres pay less attention to their appearance, especially hair care. This study aims to determine the influence of willingness factors, habit factors, social environmental factors and socio-economic factors on the hair care of PKK cadres. The research method used is quantitative with the sampling technique used is Simple Random Sampling. Based on a population of 90 people with a confidence level of 95%, a sample size of 72 people was obtained. Data processed using Multiple Linear Regression Analysis Y = 2932,968 + 0,771 X₁ + 1,013 X₂ + 0,210 X₃ + 0,225 X₄ + e. Partially, the willingness and habit factors have a significant influence on the hair care behavior of PKK cadres with the value of t count = 4.112 and 2.677 > t table = 1.996, while the social environment and socio-economic factors do not have a significant influence on the hair care behavior of PKK cadres with the value of t count = 0.777 and 0.801 < t table = 1.996. The independent variable (X) that has the most influence on the dependent variable (Y) is X1, the willingness factor with the largest standardized coefficients beta value of 0.461.